The system of linear equations

y-2x=3--(1)

3x-2y=5--(2)

substituting(1,3)in equation(1)we have

\(=>3-2(1)=3\)

\(=>-3ne3\)

substituting(1,3) in equation 2,we have

\(=>3(1)-2(3)=3\)

\(=>-3ne3\)

Given order doesn't satisfy the given system of linear equation

NO,because substituting the given ordered pair does not yield two true expressions.

y-2x=3--(1)

3x-2y=5--(2)

substituting(1,3)in equation(1)we have

\(=>3-2(1)=3\)

\(=>-3ne3\)

substituting(1,3) in equation 2,we have

\(=>3(1)-2(3)=3\)

\(=>-3ne3\)

Given order doesn't satisfy the given system of linear equation

NO,because substituting the given ordered pair does not yield two true expressions.